2013
DOI: 10.1097/wnf.0b013e31829a498d
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Antiepileptic Drugs in North Indian Pediatric Outpatients

Abstract: Monotherapy was the preferred treatment. Phenytoin was the most common ADR causative agent. Female sex, symptomatic epilepsy, and older age (> 5 years) were found to be associated with higher probability of ADR development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
4
19
1
3
Order By: Relevance
“…4 Another study in India with a different AED utilisation pattern reported a lower incidence of behavioural effects (5.7%). 38 While valproic acid and carbamazepine were the most commonly prescribed AEDs in this study, about two-third of the patients in the Indian study received phenytoin. We have reported no significant differences in cognitive and behavioural functions during and after AED treatment.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…4 Another study in India with a different AED utilisation pattern reported a lower incidence of behavioural effects (5.7%). 38 While valproic acid and carbamazepine were the most commonly prescribed AEDs in this study, about two-third of the patients in the Indian study received phenytoin. We have reported no significant differences in cognitive and behavioural functions during and after AED treatment.…”
Section: Discussionmentioning
confidence: 72%
“…There have been few pharmacovigilance studies of AEDs in children. 4 38–40 The main ADRs identified in this study were behavioural problems (12%) and somnolence/sleep problems (10%). These were also the two most common ADRs in a previous study more than 20 years ago.…”
Section: Discussionmentioning
confidence: 78%
“…If inhaled and human-metabolized CBD do not convert to Δ 9 -THC, as previous research suggests, 30 and the trace amounts of THC in plant-extracted CBD medications cannot account for the high incidence of somnolence and fatigue in recent studies, 26 , 27 the events may be partially explained by the sedating effects of antiepileptic drugs. 35 , 36 However, these effects may also be a normal response to the psychoactive Δ 9 -THC and Δ 8 -THC released from the nonpsychoactive precursor CBD in the highly acidic gut milieu. Since studies of the effects of simulated gastric juice on CBD have shown that acid degradation also yields at least two hexahydrocannabinols that have been associated with catalepsy, hypothermia, sleep prolongation, and antinociception in mice, 28 additive or synergistic activity at multiple cannabinoid receptors may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Phenytoin has a narrow therapeutic index with a large propensity to produce ADRs due to patient interindividual variability. Adverse side effects of phenytoin are common and often include rashes, headache, behavioral changes, Steven-Johnson syndrome, cardiovascular collapse, and arrhythmias, especially with rapid intravenous administration, in both children and adults (Bansal et al, 2013;Polat et al, 2015). Many pediatric patients with severe epilepsy are often treated with polytherapy, and interactions between phenytoin and other AEDs and the resulting adverse effects have been documented; for example, concurrent treatment with phenytoin and valproic acid produced phenytoin toxicity in an adolescent epileptic patient despite adhering to pediatric dosing guidelines for phenytoin (Carvalho et al, 2014).…”
mentioning
confidence: 99%